1977
DOI: 10.1042/bj1640557
|View full text |Cite
|
Sign up to set email alerts
|

Hypoketonaemic effect of L-alamine. Specific decrease in blood concentrations of 3-hydroxybutyrate in the rat

Abstract: 1. The injection of L-alanine (50-100 mg/kg) into 35-day-old rats that had been starveed for 48 h increased blood L-alanine concentration to values observed in fed animals and lowered the blood concentration of 3-hydroxybutyrate within 2 min. 2. This hypoketon aemic action of L-alanine was specific for 3-hydroxybutyrate, since the acetoacetate concentrations did not change significantly. 3. The decrease in 3-hydroxybutyrate elicited by L-alanine was not related to changes in the blood concentrations of insulin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
17
0

Year Published

1978
1978
2010
2010

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 44 publications
2
17
0
Order By: Relevance
“…Our finding that the anti-ketogenic effect involved acetoacetate as much as 3-hydroxybutyrate in the rat as well as in man is in direct contrast with the reports of Ozand et al (1977Ozand et al ( , 1978. The only major differences in experimental protocol were that our rats were older and, perhaps more importantly, we used a simultaneous infusion of somatostatin.…”
Section: Discussionmentioning
confidence: 73%
See 2 more Smart Citations
“…Our finding that the anti-ketogenic effect involved acetoacetate as much as 3-hydroxybutyrate in the rat as well as in man is in direct contrast with the reports of Ozand et al (1977Ozand et al ( , 1978. The only major differences in experimental protocol were that our rats were older and, perhaps more importantly, we used a simultaneous infusion of somatostatin.…”
Section: Discussionmentioning
confidence: 73%
“…It was deduced that this was independent of an effect on insulin. The decrease in blood ketone-body concentration caused by alanine was confirmed in the rat by Ozand et al (1977), who showed that the effect was unchanged by the presence of anti-insulin serum, suggesting more directly that insulin was not involved in the phenomenon. A notable finding of Ozand et al (1977Ozand et al ( , 1978 was that the antiketogenic effect was restricted to 3-hydroxybutyrate with blood acetoacetate concentrations remaining unchanged or even increasing.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…Alanine, one of the primary gluconeogenic substrates (Ross et al, 1967;Felig, 1975;Garber et al, 1976), is released in substantial amounts from skeletal muscle (Blackshear et al, 1975;Felig, 1975;Garber et al, 1976). In addition, the elevation of this arnino acid in blood above 0.6mm causes a marked decrease in the blood [3-hydroxybutyrate] and alters the overall production of ketone bodies (Ozand et al, 1977). These findings suggest that this amino acid may have a regulatory role in both gluconeogenesis and ketogenesis.…”
mentioning
confidence: 90%
“…Enhanced hepatic fatty acid oxidation results in the increased production of acetoacetic acid which is in turn converted to D-3-hydroxybutyric acid by a reaction catalyzed by 3-hydroxybutyrate dehydrogenase. D-3-Hydroxybutyrate represents a major form of ketone bodies, especially in such metabolic situations as starvation 1,2) and diabetes mellitus, 2) by which hepatic fatty acid oxidation is enhanced. Enzymatic methods, [3][4][5][6] which have been widely employed for the determination of this compound, involve the conversion of D-3-hydroxybutyric acid to acetoacetic acid through a reaction catalyzed by 3-hydroxybutyrate dehydrogenase, and subsequent spectrophotometric determination of the NADH produced.…”
mentioning
confidence: 99%